1) (x+2)^n-1 + (x+2)^n-2 (x+1) +(x+2)^n-3 (x+1)^2+..........(x+1)^n-1 equals to
a) (x+2)^n-1 - (x+1)^n b)(x+2)^n-1 -(x+1)^n c) none of these

2) Number of terms in a G.P. is even and sum of these terms is 5 times of sum of odd terms,then common ratio is
a) 2 b)3 c) 4 d) 5




This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
(x+2)^{n-1}+ (x+2)^{n-2}* (x+1) +(x+2)^{n-3} *(x+1)^2 \\.\ \ \ \ \ ...+(x+1)^{n-1}\\\\let\ x+2=a,\ x+1=b\\\\So\ given\ \ a^{n-1}+ a^{n-2}* b +a^{n-3} *b^2+ ...+a\ b^{n-2}+b^{n-1}\\\\=(a+b)^{n-1}=(x+2+x+1)^{n-1}\\\\=(2x+3)^{n-1}

number of terms = 2 n
T1 = a              common ratio = r
Geometric series:    a , a r, a r², .... a r^{2n-1}

sum\ S_{2n}=\frac{a(r^{2n+1}-1)}{r-1},\ \ ----(1)\\\\Series\ with\ odd\ terms:\ a, ar^2, ar^4...,ar^{2n-2}\\Common\ ratio=r^2\\\\Sum\ S_{n\ odd\ terms}=\frac{a((r^2)^{n+1}-1)}{r^2-1},\ \ ----(2)

Sum of even terms + sum of odd terms = sum of all terms = 5 * sum of odd terms
   =>  Sum of even terms = 4 * sum of odd terms 

even\ terms\ series:\ ar^2,ar^4,ar^6,...,ar^{2n-1}\\Common\ ratio=r^2,\ \ T_1=ar^2\\\\Sum\ S_{n\ even\ terms}=\frac{ar^2((r^2)^{n+1}-1)}{r^2-1}=\frac{ar^2(r^{2n+2}-1)}{r^2-1},\ \ \ ---(3)

\frac{S_{n\ even\ terms}}{S_{n\ odd\ terms}}=4=r^2

Hence,  r = +2 or -2

2 5 2
click on thanks button above pls
select best answer please